Case Report- Prevention strategies for permanent tracheostomy tube migration into the left main bronchus in tracheostomized patients [version 1; peer review: 2 approved] - Said Khallikane; Monsif Salek; Younès Aissaoui; Amine Bentahar; Ayoub Belhadj (F1000Research)
Tracheostomy tube migration is a rare but potentially life-threatening complication. We present the case of a 66-year-old male with chronic obstructive pulmonary disease, dual-chamber pacemaker implantation for chronic ischemic cardiomyopathy, and supraglottic squamous cell carcinoma. The patient developed respiratory distress due to intrabronchial migration of the tracheostomy tube. Initial evaluation revealed significant respiratory effort, inspiratory stridor, and an absent tube at the stoma site. Imaging and bronchoscopy confirmed the tube’s presence in the left main bronchus with associated mucosal inflammation. The patient underwent bronchoscopic-guided tube removal and successful repositioning of a cuffed tracheostomy tube under spontaneous ventilation anaesthesia. Following stabilization, he was discharged with plans for a permanent tracheostomy. Tracheostomy tube migration presents a significant diagnostic and therapeutic challenge, particularly given the scarcity of studies involving adults with this complication. This case highlights the importance of early recognition, prompt imaging—especially bronchoscopy—and tailored management strategies, while emphasizing the active involvement of the patient and family in the care pathway. It also underscores the necessity for vigilant monitoring to prevent severe, potentially fatal, complications.